2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944004
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated signals from a long-term Regenerative Peripheral Nerve Interface

Abstract: Despite modern technological advances, the most widely available prostheses provide little functional recovery beyond basic grasping. Although sophisticated upper extremity prostheses are available, optimal prosthetic interfaces which give patients high-fidelity control of these artificial limbs are limited. We have developed a novel Regenerative Peripheral Nerve Interface (RPNI), which consists of a unit of free muscle that has been neurotized by a transected peripheral nerve. In conjunction with a biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…26,41 Indeed, RPNIs can conduct and amplify nerve signals 44 to support real-time intuitive control of advanced myoprostheses. 45,46 More recent studies have demonstrated muscle reinnervation by sensory nerves as well, which may prove useful in achieving bioprosthetic somatosensory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…26,41 Indeed, RPNIs can conduct and amplify nerve signals 44 to support real-time intuitive control of advanced myoprostheses. 45,46 More recent studies have demonstrated muscle reinnervation by sensory nerves as well, which may prove useful in achieving bioprosthetic somatosensory feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The reinnervated muscle prevents neuroma and is a durable site for electrode implantation, thus avoiding iatrogenic axonal injury that can occur when electrodes are directly interfaced with peripheral nerve. 15 We have demonstrated long-term RPNI viability and EMG signal transduction 12,16 ; however, the most appropriate electrode type and recording configuration for high-fidelity signal transduction using RPNIs has not yet been determined. In this pilot study, we evaluated the performance of two of the most accepted electrode designs-an epimysial patch and an intramuscular hook electrode-for signal recording performance during chronic skeletal muscle implantation.…”
Section: Discussionmentioning
confidence: 99%
“…For purposes of the RPNI, a decrease in signal-of-interest amplitude is not desired; however, signal amplitudes in this study remained sufficiently large to control myoprostheses. 16 Furthermore, small losses of bioelectric signals are acceptable if the signal-to-noise ratio remains high enough such that EMGs responsible for independent functions are easily discriminated from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is the regenerative peripheral nerve interface (RPNI), developed by Paul Cederna et al, wherein nerve fascicles are implanted into muscle grafts, each with its own electrode. 179 Although it is still being optimized, RPNI has proven viable for more than a year in a rodent model, with muscle reinnervation and consistently detectable muscle activity during implantation. 179182 …”
Section: Current Interfaces In the Pnsmentioning
confidence: 99%
“…179 Although it is still being optimized, RPNI has proven viable for more than a year in a rodent model, with muscle reinnervation and consistently detectable muscle activity during implantation. 179182 …”
Section: Current Interfaces In the Pnsmentioning
confidence: 99%